"Water, water everywhere, nor any drop to drink": An exploration of the lack of a formal global water governance regime. - Newton, Joshua. (2017)
Abstract: Global water governance has only recently emerged as a focus of study. This is in large part due to a lack of recognition of the importance of water at the global level, because historically water has always been dealt with at the local, national and basin levels. Global processes impact water use in basins more today than ever before. Because of globalization, there is increasing mutual interdependencies between states and their water resources and increased competition over resources due to growing populations and economic development. Global water governance will be an important factor in addressing water issues in the future as it has the ability to optimize water resource use through coordination, stewardship and knowledge exchange. While global water governance exists informally through a patchwork of principles, practice and actors, why does a more formal global water governance regime not exist? Could a more formal global water governance regime help address the emerging global water crisis? To answer these questions, interviews were conducted with over 130 water professionals from international organizations, governments, NGOs and the private sector, exploring the influence and impacts of events, organizations and issues on the trajectory of global water governance. Through their experiences in and perceptions of the current global water situation, a view emerged of how the world has arrived at the fragmented, piecemeal governance system that exists for water. Water, a means to many ends, is not an easy resource to govern because it serves many purposes and does not respect political borders yet is viewed by many as a key to national security. Issues of sovereignty and competition, both at international and organizational levels, dominate the water community and combined with the complex nature of water, lack of leadership and how water has been dealt with through a sectoral approach, the world has yet to come together in a cohesive, coordinated manner to address the emerging global water crisis. A qualitative analysis of the interviews showed that water governance at the global level should not aim to create a single UN agency for water or a global water convention, but to "enhance the patchwork" through capitalizing on the increasing convergence and coordination in the water community and on key issues and priorities that has occurred through the Post-2015 Development Agenda process, that can lead to a flexible, comprehensive governance framework that optimizes action amongst myriad actors.; Thesis (Ph.D.)--Tufts University, 2014.; Submitted to the Dept. of Diplomacy, History, and Politics.; Advisor: William Moomaw.; Committee: Kelly Sims Gallagher, and Aaron Wolf.; Keyword: International relations.